Consensus protocol for EEG and amplitude-integrated EEG assessment and monitoring in neonates. Issue 4 (April 2021) - Dilena, Robertino; Raviglione, Federico; Cantalupo, Gaetano; Cordelli, Duccio M.; De Liso, Paola; Di Capua, Matteo; Falsaperla, Raffaele; Ferrari, Fabrizio; Fumagalli, Monica; Lori, Silvia; Suppiej, Agnese; Tadini, Laura; et al.
Highlights: This paper is a consensus statement on neonatal EEG and aEEG written by an Italian interdisciplinary working group. A systematic review of literature and discussions among experts took place to elaborate shared recommendations. We provide a flexible frame of recommendations applicable by neonatal units according to local resources and patient features. Abstract: The aim of this work is to establish inclusive guidelines on electroencephalography (EEG) applicable to all neonatal intensive care units (NICUs). Guidelines on ideal EEG monitoring for neonates are available, but there are significant barriers to their implementation in many centres around the world. These include barriers due to limited resources regarding the availability of equipment and technical and interpretive round-the-clock personnel. On the other hand, despite its limitations, amplitude-integrated EEG (aEEG) (previously called Cerebral Function Monitor [CFM]) is a common alternative used in NICUs. The Italian Neonatal Seizure Collaborative Network (INNESCO), working with all national scientific societies interested in the field of neonatal clinical neurophysiology, performed a systematic literature review and promoted interdisciplinary discussions among experts (neonatologists, paediatric neurologists, neurophysiologists, technicians) between 2017 and 2020 with the aim of elaborating shared recommendations. A consensus statement on videoEEG (vEEG) and aEEG for the principal neonatal indications was established. The authors propose a flexible frame of recommendations based on the complementary use of vEEG and aEEG applicable to the various neonatal units with different levels of complexity according to local resources and specific patient features. Suggestions for promoting cooperation between neonatologists, paediatric neurologists, and neurophysiologists, organisational restructuring, and teleneurophysiology implementation are provided.